Differences in perceived readiness to train between two menstrual cycle phases in Division II female athletes - Reinertz, N.; Crossland, B. D. (International Journal of Exercise Science Conference Proceedings, 2025)
Recently, the effects of the menstrual cycle (MC) and hormonal fluctuations on performance outcomes and training readiness have received significant research focus, leading to the potential for more individualized and informed approaches in athlete training. Training readiness refers to an athlete´s state of balance between their current training load, fatigue, and potential risk of injury or illness. The MC is divided into two phases (± 28 days), commencing with the follicular or proliferative phase (days 1 to 13) followed by the luteal phase, also known as the secretory phase (days 14 to 28). Its hormonal fluctuation throughout the cycle can significantly affect an athlete´s readiness and thereby directly influencing overall performance outcomes.